Histamine H3 receptor antagonist E177 attenuates amnesia induced by dizocilpine without modulation of anxiety-like behaviors in rats - Alachkar A (Dove Medical Press, 2019)
Alaa Alachkar,1 Nadia Khan,1 Dorota Łażewska,2 Katarzyna Kieć-Kononowicz,2 Bassem Sadek1 1Department of Pharmacology and Therapeutics, College of Medicine and Health Sciences, United Arab Emirates University, Al Ain, United Arab Emirates; 2Department of Technology and Biotechnology of Drugs, Faculty of Pharmacy, Jagiellonian University Medical College, Kraków, Poland Background: Alzheimer disease (AD) is the main cause of dementia in elderly people. The potential of histamine H3 receptor (H3R) antagonists as a pharmacological treatment of several neuropsychiatric diseases is well established. Methods: The novel non-imidazole-based H3R antagonist E177 was screened for its procognitive effects on the inhibitory avoidance paradigm (IAP) and novel object recognition (NOR) task in a dizocilpine (DIZ)-induced model of amnesia in male Wistar rats. Donepezil, an acetylcholine esterase inhibitor, was used as the reference drug. Results: Acute systemic treatment with E177 (1.25, 2.5, 5, and 10 mg/kg intraperitoneally [i.p.]) significantly attenuated the cognitive impairments induced by DIZ in the IAP (all P-values <0.05, n=7), and the protective effect of the most promising dose of E177 (5 mg/kg) was abrogated when H3R agonist R-(α)-methylhistamine (RAMH; 10 mg/kg i.p.) was co-administered (P=0.281 for DIZ-amnesia group vs DIZ + E177 + RAMH group, n=7). The discrimination index calculated for E177 (5 mg/kg, i.p.) showed a significant memory-enhancing effect on DIZ-induced short-term memory impairment in the NOR task (P<0.05, n=6), with the enhancement nullified when animals were co-administered RAMH (10 mg/kg). Moreover, the results revealed that E177 (5 and 10 mg/kg, i.p.) did not alter the anxiety levels and locomotor activity of animals naïve to the open-field test (all P-values >0.05, n=8) or the elevated plus maze test (all P-values >0.05, n=6–8), which indicated that the E177-induced enhancement of memory performance in the IAP or NOR task was unrelated to changes in emotional response or in spontaneous locomotor activity. Conclusion: The observed results suggested a possible contribution of H3Rs in the alteration of brain neurotransmitters that accompany neurodegenerative diseases, such as AD. Keywords: Histamine H3 receptors, antagonist, dizocilpine-induced amnesia, inhibitory avoidance paradigm, novel object recognition, elevated plus maze, open field test, memory, anxiety